Synthesis and Electrochemical Characterization of NiCo\(_2\)S\(_4\) Nanosheets/reduced Graphene Oxide for Energy Storage Applications - Le, Thi Thanh Tam; Doan, Thanh Tung; Ngo, Thanh Dung; Phan, Ngoc Hong; Pham, Van Hoi; Phan, Ngoc Minh; Le, Trong Lu (Communications in Physics, 2020)
In the present study, NiCo2S4-rGO (NCS-rGO) composites were fabricated by mixing active materials including NCS and rGO individually using polyvinypyrrolidone (PVP) as a binder to form a homogeneous mixture. Therein, rGO was prepared by modified Hummer’s method while NCS nanosheets were successfully synthesized by thermal decomposition method using 1-dodecanethiol (DDT) as a sulfur source. The NCS-rGO composites based electrode was then produced using 3D printing technique making easy to design electrodes with the desired shape. The architecture and elemental composition of electrode components are characterized by energy dispersive x-ray analysis (EDX) and scanning electron microscopy (SEM). The electrochemical activity of the NCS-rGO electrode were studied in three electrode configuration in 6M KOH electrolyte by CV, GCD and EIS measurement. The obtained results indicate that the combination of NCS nanosheets and rGO could improve the electrical conductivity of the individual materials, enhance electrochemical performance of electrode. The as-prepared NCS-rGO electrode posseses a high Csp of 1535.8 Fg-1 at 4 Ag-1 with excellent cycling stability even after 2500 charge-discharge cycles,  demonstrating that the NCS-rGO nanocomposites  are promising candidates for electrode materials for high-performance energy storage devices in the future.